The Use of Instructional Media in PAI (Islamic Religious) Lesson in Elementary School - Ahmad Munjin Nasih; Achmad Sultoni; Maisyaroh; Ah. Zakki Fuad; Ali Rif’an (JPP (Jurnal Pendidikan dan Pembelajaran), 2017)
The teaching of Islamic education in elementary school in Indonesia has not been widely explored by researchers, while this subject is particularly important in developing students’ character. This study aimed to describe the teaching of Islamic Education in elementary school in Malang, particularly in terms of the use of instructional media. Qualitative method with case study observational design and multi-site research design was chosen to meet the aim, including the use of structured-interview and observation as means of data collection. By using qualitative data analysis, it was found that (1) there were diverse teaching methods used by teachers, (2) teachers used various instructional media, both conventional and modern, (3) the quantity and quality of supporting facilities of the PAI lesson were considered sufficient, and (4) there were some internal as well as external factors that either supported or hampered the teaching of Islamic Education in elementary school.